Yoga como terapia complementaria en el tratamiento de pacientes con diabetes mellitus tipo 2. - Querido Falcón, Silvia Patricia (2024)
Introduction: Yoga is an age-old practice that includes physical postures, breathing techniques, and meditation and has proven to be an effective adjunctive therapy in treating type 2 diabetes mellitus. Combining asanas (postures), pranayama (breathing techniques), and meditation helps improve blood glucose control, increases insulin sensitivity, and improves patients' quality of life. Recent studies have confirmed that regular yoga practice can reduce glycosylated hemoglobin (HbA1c) and fasting glucose levels, optimize insulin sensitivity, and decrease stress levels, which are crucial factors in diabetes management. Patients who include yoga in their daily routine report a marked improvement in their physical and mental well-being. Objective: To describe the effects of yoga as a complementary treatment in the glycemic control of patients with type 2 diabetes mellitus. Method: A bibliographic search was carried out by collecting scientific articles corresponding to clinical trials to obtain the necessary information on yoga in treating type 2 diabetes mellitus under the parameters of the PEDro scale. In addition, keywords were determined as, "yoga," "diabetes mellitus type 2," "complementary therapy," "glycemic control," "insulin sensitivity," "quality of life," "yoga AND diabetes," "' yoga OR diabetes' 'types of diabetes.' Boolean operators such as AND, OR and NOT were also used. Results: To determine the outcome, 25 articles were collected for documentary literature research that showed that the groups who practiced yoga regularly significantly decreased HbA1c and fasting glucose levels compared to the control group. In addition, they observed an improvement in insulin sensitivity and a greater perception of well-being and quality of life in the group that practiced yoga. Conclusions: Yoga can be an effective adjunctive therapy for managing type 2 diabetes mellitus. The inclusion of this practice in complementary treatment can significantly improve glycemic control and quality of life of patients.